Value profile and corruption propensity correlates among employees in two types of government agencies - Enriquez, Virgilio G. (Philippine Journal of Public Administration, 1995)
Corruption, a perennial problem besetting the Philippine bureaucracy, is once more explored from a psychological perspective. Values espoused bureaucrats and their corrupt practices, if any, are correlated using the Philippine Value Orientation Inventory (PVOI) research instrument in testing corruption prone and noncorruption prone agencies. One significant conclusion derived from the study is that propensity and propinquity reinforce a culture of corruption within corruption prone agencies.